WORLD EXPERIENCE: THE LINKAGE BETWEEN DIGITAL TRANSFORMATION AND GROWTH (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This paper examines how digital transformation shapes economic growth by changing productivity dynamics, firm behavior, public service efficiency, and the allocation of capital and labor. Drawing on international experience, the study frames digital transformation as a systemic shift that combines infrastructure (broadband, cloud, data centers), adoption (digital skills, e-commerce, automation), and governance (competition policy, cybersecurity, data protection, and digital public platforms). The central argument is that growth effects depend less on technology availability and more on diffusion quality: complementary investments in human capital, management practices, and institutions determine whether digital tools translate into higher total factor productivity and inclusive gains. The paper also highlights common bottlenems: unequal connectivity, skill gaps, low trust in digital services, and weak interoperability across public and private systems, which can slow diffusion and widen regional and sectoral disparities. The analysis positions Uzbekistan’s reform trajectory within these global patterns and proposes a policy-informed lens for assessing which digital levers most reliably generate growth, employment upgrading, and resilience in emerging economies.
Keywords: Digital transformation, economic growth, productivity, total factor productivity, ICT infrastructure, diffusion, innovation, platform economy, digital skills, e-government, competitiveness, data governance, cybersecurity, inclusive development, structural change.